The Role Of Parents In Supporting The Use Of "Healthy Internet" In Early Childhood - Laros Tuhuteru; Jihan Jihan; Gamar Al Haddar; Irmawati S; Firman Aziz (Journal on Education, 2023)
Children find a wide range of information and entertainment on the internet to be highly engaging, but sadly not all of it is appropriate or good for them. Hence, it is crucial that parents play a proactive part in encouraging children to use the internet responsibly. In order to ensure that their children use the internet safely and sensibly, parents play an important role. Parents should take an active role by keeping an eye on online activities, educating children about safe and responsible internet use, establishing clear rules and boundaries, talking to their kids, and teaching them about morality and ethics online. Based on the literature review, this research aims to be able to provide a scientific point of view related to the role of parents in implementing a healthy internet for kids. By understanding the role, specific objectives related to the role of parents related to knowledge transfer to kids and things that can be done in supervising internet usage can be determined in order to maximize kids' potential in using technology from a young age